Potential Effects of Live and Nutrient-Enhanced Food on Growth Performance and Biochemical Composition of Blue Acara (Andinoacara pulcher) - Siva Santhiya R.; Aiswarya M. V.; Mary Mettilda Bai S.; Vinoliya Josephine Mary J.; Citarasu T.; Uma G.; Anusha J. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fish food and feeding play an important role in understanding the rate of growth, development and reproduction in ornamental fish culture. The current study evaluated the impact of different types of food on the growth of Ornamental fish, Andinoacara pulcher. A comparative analysis of live, prepared, and commercial food was conducted in three feeding groups A, B and C, respectively. For live feed, Artemia larvae were cultured from Artemia seeds, and fed. The growth in terms of weight and body length was measured at 15-day intervals throughout the experimental period of 60 days. In addition, the protein, lipid, ash, and moisture composition of fish were estimated and analyzed. From the results, the fish fed with live artemia feed attained maximum growth when compared to other prepared feed and commercial feed. The specific growth rate (SGR) was found to be maximum in group A (1.46%), followed by group B (1.15%) and group C (0.71%). There is a well-defined relationship between the rate of growth and the type of food consumed. The protein, carbohydrate, and fat content of fish revealed a higher biochemical composition. In conclusion, the growth and biochemical study in the present investigation indicated that the live feed contains good constituents of vital nutrient substances that promote the growth and protein content of ornamental fish, Blue Acara.